Understanding the Organizational Barriers of Promoting Electronic Delivery Options in the United States Health Care System: An Insurer’s Perspective - O'Leary, Danielle A.; Kiel, Joan M (Journal of Information Systems and Technology Management, 2019)
Consumer-driven technologies are rapidly transforming how industries conduct business both internally and externally. From online banking to retail, the broad adoption of smart devices, internet access, and wearables amongst consumers has shifted the way enterprises develop software and conduct information technology (IT) operations. Although successful adoption of consumer-driven technologies is a reality for many industries, the healthcare platform is lagging. The promotion and adoption of online patient engagement is widely perceived to be one of the biggest hurdles faced by healthcare organizations (Carr, 2014). While setting up patient portals and electronic delivery options can be relatively simple, promoting consumer utilization and achieving widespread use of these portals use has posed challenges. The healthcare paradigm has shifted in recent decades from viewing the patient as incidental to the delivery of healthcare to a more patient-centric approach. The previous model of indirectly funding Medicare, Medicaid, or employers has been noted as one of the greatest flaws of the healthcare system by contributing to cost inflation (Carr, 2014). Recent trends have promoted patient-empowered care, but have generally transferred the burden of cost to the individual. The Affordable Care Act (ACA) stimulated this shift by creating insurance exchanges which allow insurers to directly reach consumers; however, these readily-available healthcare options now require higher monthly premium payments from shoppers. This new model proposes that as patients become increasingly financially liable, they become more invested in their healthcare trajectories.